PENGARUH AKUNTABILITAS TERHADAP EFEKTIVITAS PENGADAAN BARANG DAN JASA PEMERINTAH PADA DIREKTORAT PEMBINAAN PENDIDIKAN KHUSUS DAN LAYANAN KHUSUS PENDIDIKAN DASAR - Hamid Hamid (Sekolah Pascasarjana UNAS, 2016)
This study aimed to examine the effect of accountability for the effectiveness of the procurement of goods and services by government accounting standards in the Directorate of Special Education and Special Services Education Association. The research population is the apparatus associated with the procurement of goods and services in the Directorate of Special Education and Special Services Basic Education that the number of population as many as 1504 people, consisting of 14 elements Chief Directorate of Special Education and Special Services, and 1400 agencies and 90 partner procurement government goods and services. While the sample in this study were 316 respondents consisting of 3 Chief Directorate of Special Education and Special Services, 294 persons from the institution, and 19 people from the working partners of government procurement. The data in this study are primary data. Data were collected using questionnaires distributed directly to the respondents. Research results and quantitative test shows that there is accountability dignifikan influence on the effectiveness of 27.5%. The existence of a causal relationship between the accountability of the effectiveness of 0.525%. And based on the regression equation to a positive value of 0.471%, this shows if accountability is increased then the increase will be followed by effectiveness. Keywords : Accountability, effectiveness, Procurement